2015
DOI: 10.1103/physrevlett.115.091601
|View full text |Cite
|
Sign up to set email alerts
|

String Theory Origin of DyonicN=8Supergravity and Its Chern-Simons Duals

Abstract: We clarify the higher-dimensional origin of a class of dyonic gaugings of D = 4 N = 8 supergravity recently discovered, when the gauge group is chosen to be ISO(7). This dyonically-gauged maximal supergravity arises from consistent truncation of massive IIA supergravity on S 6 , and its magnetic coupling constant descends directly from the Romans mass. The critical points of the supergravity uplift to new AdS4 massive type IIA vacua. We identify the corresponding CFT3 duals as superChern-Simons-matter theories… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
493
0
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 146 publications
(508 citation statements)
references
References 37 publications
12
493
0
3
Order By: Relevance
“…In [3] the authors showed that a consistent truncation of a massive type IIA SUGRA on the six sphere S 6 gives rise to the ISO(7)-dyonically-gauged SUGRA with the magnetic coupling constant related to the Romans mass. They also showed that this supergravity solution has a fixed point which uplifts to a new N = 2 AdS 4 × SS 5 solution, where SS 5 is the suspension of S 5 and is topologically equivalent to the six sphere S 6 [20].…”
Section: Guarino-jafferis-varela Solution and Duality To Sym-csmentioning
confidence: 99%
See 4 more Smart Citations
“…In [3] the authors showed that a consistent truncation of a massive type IIA SUGRA on the six sphere S 6 gives rise to the ISO(7)-dyonically-gauged SUGRA with the magnetic coupling constant related to the Romans mass. They also showed that this supergravity solution has a fixed point which uplifts to a new N = 2 AdS 4 × SS 5 solution, where SS 5 is the suspension of S 5 and is topologically equivalent to the six sphere S 6 [20].…”
Section: Guarino-jafferis-varela Solution and Duality To Sym-csmentioning
confidence: 99%
“…where F (6) = −e φ/2 * F 4 , and the Hodge dual is taken with relation to the Einstein frame metric (2.1a), as the authors of [3] have shown. This integer will correspond to the rank of the gauge group in the field theory.…”
Section: Jhep07(2017)020mentioning
confidence: 99%
See 3 more Smart Citations